Profile of High School Students’ Mathematical Beliefs in the “Quitter” Category of the Adversity Quotient - Komang Tri Ananda Kusuma; Pathuddin Pathuddin; Mubarik Mubarik; I Nyoman Murdiana (FKIP - Universitas Riau, 2026)
This study aimed to describe students’ mathematical beliefs, particularly in the aspect of mathematical social norms, among students categorized as quitter based on the Adversity Quotient. This study employed a qualitative descriptive approach. The subject was one eleventh grade student categorized as a quitter selected through the Adversity Response Profile (ARP) questionnaire, mathematics teacher recommendations, and willingness to participate in the study. Data were collected through classroom observations and semi structured interviews. The findings showed that the quitter student demonstrated positive mathematical beliefs regarding mathematical social norms during mathematics learning. The student was able to accept differing opinions, participate in collaborative discussions, ask and answer questions to understand mathematical concepts, communicate ideas systematically and politely, and apply mathematical symbols and principles consistently during problem solving. These findings highlight that student categorized as quitter may still demonstrate positive mathematical social norms despite having low Adversity Quotient characteristics. However, these findings are limited to the quitter category involved in this study and cannot be generalized to students with different Adversity Quotient characteristics.